Feasibility Study of Islamic Propagation Institutions in Entrepreneurship in the Disruptive Era - Hardi, Luthfi; Castrawijaya, Cecep (Contemporary Journal of Applied Sciences, 2024)
The feasibility study of entrepreneurship in da'wah institutions aims to explore the potential for developing entrepreneurship as a strategy to enhance the competitiveness and sustainability of such institutions. Da'wah institutions, which play a crucial role in spreading religious values, must adapt to the changing times. One way to achieve this is by integrating entrepreneurship while maintaining their religious mission and contributing to the local economy. This study employs a descriptive qualitative method to examine the feasibility of da'wah institutions undertaking entrepreneurial activities amidst the disruptive era. The findings provide critical insights for managers or leaders of da'wah institutions in formulating effective entrepreneurial strategies to remain relevant and positively impact society during rapid change